Effect of food on the pharmacokinetics of omeprazole, pantoprazole and rabeprazole - Dolores Ochoa; Manuel Román; Teresa Cabaleiro; Miriam Saiz-Rodríguez; Gina Mejía; Francisco Abad-Santos (BMC, 2020)
Abstract Background The pharmacokinetics of proton pump inhibitors (PPIs) may be affected by food intake. We aimed to evaluate the effect of food on the pharmacokinetics of omeprazole, rabeprazole, and pantoprazole. Setting The study population comprised 186 healthy volunteers participating in 6 bioequivalence clinical trials. Method Subjects were evaluated to determine the effect of a high-fat breakfast on the pharmacokinetics of omeprazole (n = 36), rabeprazole (n = 69), and pantoprazole (n = 81). Main outcome measure Drug plasma concentrations were measured using high-performance liquid chromatography coupled to mass spectrometry. Results Food affected the pharmacokinetics of omeprazole (increased Tmax and decreased AUC and Cmax), pantoprazole (increased Tmax and decreased AUC), and rabeprazole (increased Tmax, Cmax and half-life). Food increased variability in Tmax for all 3 drugs, delaying absorption around 3 to 4 h and until 20 h in some subjects. Conclusion As food delays the absorption of PPIs and increases their variability, it would be better to administer these drugs under fasting conditions. Trial registration European Union Drug Regulating Authorities Clinical Trials Database: EudraCT : 2004-003863-59 (registration date 05/MAR/2004), EudraCT 2006-001162-17 (registration date 17-MAR-2006), EudraCT: 2007-002489-37 (registration date 12-JUN-2007), EudraCT: 2007-002490-31 (registration date 12-JUN-2007), EudraCT: 2010-024029-19 (registration date 23-NOV-2010).